Editorial Vol16 no3 - Alan MacQuarrie (Scottish Journal of Residential Child Care)
I am grateful to the editors of the Scottish Journal of Residential Child Care for inviting me to edit this special themed edition on historical research and historical subjects. It has been an enriching experience to see the research which is being carried out and the lessons which are being learned from it.